Peranan Housekeeping dalam Peningkatan Kualitas Pelayanan Tamu di Hotel Swarna Dwipa Palembang - Anjelika Utami; Akhmad Khudri (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the role of the housekeeping department in improving guest service quality at Hotel Swarna Dwipa Palembang, a three-star hotel operating in an increasingly competitive hospitality industry. Guest service quality, particularly related to room cleanliness, tidiness, and comfort, is a crucial factor influencing guest satisfaction, hotel image, and customer loyalty. This research employs a qualitative descriptive approach with data collected through direct observation, semi-structured interviews, and documentation. The research subjects include the Housekeeping Manager, supervisors, room attendants, and hotel guests with direct stay experiences. The findings indicate that housekeeping plays a strategic role in maintaining room quality through the implementation of standard operating procedures (SOPs), meticulous room and bathroom cleaning, proper linen arrangement, and prompt responses to guest complaints. Nevertheless, several challenges were identified, such as limited human resources, high workload during peak occupancy, and inconsistency in maintaining detailed cleanliness standards. An effective housekeeping role has been proven to enhance guest comfort, create positive impressions, and strengthen the image of Hotel Swarna Dwipa Palembang as a clean and comfortable hotel. This study is expected to serve as an evaluation and recommendation for hotel management in improving service quality, particularly within the housekeeping department, to support sustainable guest satisfaction and loyalty.